Penerapan Model Pembelajaran Ttw (Think Talk Write) Dalam Meningkatkan Hasil Belajar Siswa Kelas X Iis 1 Sma Negeri 2 Kulisusu Pada Mata Pelajaran Geografi - Wati, Trisna; Kasmiati, Sitti; Nursalam, La Ode (UNIVERSITAS NEGERI MAKASSAR, 2019)
SMA Negeri 2 Kulisusu is one of the schools in North Buton Regency which is the object of research by researchers because student learning outcomes are still low. The purposes of this study are: (1) To see a picture of student learning activities through the application of the Think Talk Write (TTW) learning model in class X IIS 1 of SMA Negeri 2 Kulisusu; (2) To see the description of teacher teaching activities through the application of the Think Talk Write (TTW) learning model in class X IIS 1 of SMA Negeri 2 Kulisusu; (3) To see a picture of an increase in the learning outcomes of grade X IIS 1 students at SMA Negeri 2 Kulisusu by using the Think Talk Write learning model. The data in this study are qualitative and quantitative data obtained from observation sheets and learning outcomes tests. Based on the results of data analysis, it was found that: (1) in the first cycle the average score of student learning activities was 2,4 which was categorized sufficiently increased in the second cycle to 3,6 which was categorized as good; (2) in the first cycle the average score of the teaching activities of the teachers was 2,5 which was categorized sufficiently increased in the second cycle to 3,6 which was categorized as good; and (3) an increase in geography learning outcomes of students of class X IIS 1 of SMA Negeri 2 Kulisusu from cycle I to cycle II. In the first cycle showed that 21 students who scored 75 with an average value of 75,3. Furthermore, the results of the second cycle test showed a significant increase because there were 28 students who scored 75 with an average score of 81,3.